2021
DOI: 10.3390/rs13183606
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spill Identification from SAR Images for Low Power Embedded Systems Using CNN

Abstract: Oil spills represent one of the major threats to marine ecosystems. Satellite synthetic-aperture radar (SAR) sensors have been widely used to identify oil spills due to their ability to provide high resolution images during day and night under all weather conditions. In recent years, the use of artificial intelligence (AI) systems, especially convolutional neural networks (CNNs), have led to many important improvements in performing this task. However, most of the previous solutions to this problem have focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Some examples regarding advanced on-board processing operations, mainly based on NN algorithms, can be found in the literature: Yao et al proposed an on-board ship detection scheme to achieve near real-time on-board processing by small satellites computing platform [18], while Zhang et al suggested a similar technique for cloud detection [19]. In [20], Del Rosso et al implemented an algorithm based on convolutional neural networks for volcanic eruptions detection based on Sentinel-2 and Landsat-7 optical data, while Diana et al used SAR images to identify oil spills through a CNN algorithm [21]. A procedure based on self-organizing maps is proposed in [22] by Danielsen et al to cluster hyperspectral images on-board, and, in [23], Rapuano et al successfully designed a hardware accelerator based on field programmable gate arrays (FPGAs) specifically made for the space environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples regarding advanced on-board processing operations, mainly based on NN algorithms, can be found in the literature: Yao et al proposed an on-board ship detection scheme to achieve near real-time on-board processing by small satellites computing platform [18], while Zhang et al suggested a similar technique for cloud detection [19]. In [20], Del Rosso et al implemented an algorithm based on convolutional neural networks for volcanic eruptions detection based on Sentinel-2 and Landsat-7 optical data, while Diana et al used SAR images to identify oil spills through a CNN algorithm [21]. A procedure based on self-organizing maps is proposed in [22] by Danielsen et al to cluster hyperspectral images on-board, and, in [23], Rapuano et al successfully designed a hardware accelerator based on field programmable gate arrays (FPGAs) specifically made for the space environment.…”
Section: Introductionmentioning
confidence: 99%